DOMINANSI, KEKAYAAN DAN KEMERATAAN JENIS VEGETASI HUTAN PANTAI TINGKAT PERMUDAAN DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Komul, Yulianus Dominggus; Sahupala, Andjela; Siahaya, Troice Elsye; Sahupala, George Loudewik (Universitas Tanjungpura, 2024)
Coastal forest vegetation on sandy and rocky soil above the coastline. Its presence is scattered along the coastline with different variations according to the coastal topography. The existence of the coastal forest in the coastal village of Kairatu with its vegetation also makes a difference to the species and types contained therein. This study aims to analyze the value of dominance, richness and evenness of tree species at the growth rate of youth spread along the coastline of Hatusua, Waipirit and Kairatu Villages in Kairatu District, West Seram Regency. Survey Method Continuous Line Plot sampling is applied to obtain data, with the length of the line adjusted to the length of the long line. Based on the results of analysis of research data on vegetation at the regeneration level (Seedlings, Saplings and Poles) the value of the species dominance index (C) was obtained between 0.0148